2018
DOI: 10.2196/mhealth.9884
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Feasibility of Monitoring Resting Heart Rate Using a Wearable Activity Tracker in Patients With Thyrotoxicosis: Prospective Longitudinal Observational Study

Abstract: BackgroundSymptoms and signs of thyrotoxicosis are nonspecific and assessing its clinical status is difficult with conventional physical examinations and history taking. Increased heart rate (HR) is one of the easiest signs to quantify this, and current wearable devices can monitor HR.ObjectiveWe assessed the association between thyroid function and resting HR measured by a wearable activity tracker (WD-rHR) and evaluated the clinical feasibility of using this method in patients with thyrotoxicosis.MethodsThir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…According to studies by Lee et al [ 17 ], McNamara et al [ 30 ], and Cruz [ 31 ], the feasibility of a wrist-worn wearable relies heavily on its accuracy, acceptability, applicability, and usefulness. At the end of the PE lessons, the students and their teachers completed a questionnaire with the help of trained staff.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to studies by Lee et al [ 17 ], McNamara et al [ 30 ], and Cruz [ 31 ], the feasibility of a wrist-worn wearable relies heavily on its accuracy, acceptability, applicability, and usefulness. At the end of the PE lessons, the students and their teachers completed a questionnaire with the help of trained staff.…”
Section: Methodsmentioning
confidence: 99%
“…It is common to evaluate physical activity via HR monitoring, and HR measurements can provide a lot of information about the intensity of physical activity [ 17 ]. Monitoring HR can help teachers determine students’ levels of physical activity and improve PE lessons.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated medical applications of the biosignal-monitoring ability of activity trackers, but only one study has done so with a focus on thyroidology. Lee et al [35] reported the clinical feasibility of monitoring resting HR using a wearable activity tracker in patients with thyrotoxicosis. In their study, they used Fitbit™ devices (Fitbit, San Francisco, CA, USA), which can measure HR and physical activity using photoplethysmography and a 3-axis accelerometer, respectively.…”
Section: Wearables and Thyroid Diseasementioning
confidence: 99%
“…It is more common in women as compared to men. 6 Grave's disease is the most common etiology of thyrotoxicosis, followed by toxic multi-nodular goiter and toxic adenoma. Other causes include thyroiditis, subacute thyroiditis, gestational hyperthyroidism and drug induced thyrotoxicosis (example amiodarone).…”
Section: Introductionmentioning
confidence: 99%
“…Other causes include thyroiditis, subacute thyroiditis, gestational hyperthyroidism and drug induced thyrotoxicosis (example amiodarone). [6][7][8] Studies have shown a genetic predisposition to Graves's disease. 7 Patients can present with a wide range of symptoms which include irritability, sweating, heat intolerance, palpitations, fatigue, anxiety and breathlessness.…”
Section: Introductionmentioning
confidence: 99%